Prevalence of cognitive impairment in Chinese older inpatients and its relationship with 1-year adverse health outcomes: a multi-center cohort study - Li Yuan; Xiaoming Zhang; Na Guo; Zhen Li; Dongmei Lv; Hui Wang; Jingfen Jin; Xianxiu Wen; Shengxiu Zhao; Tao Xu; Jing Jiao; Xinjuan Wu (BMC Geriatrics, 2021)
Abstract Background Previous studies on the relationship between cognitive impairment and adverse outcomes among geriatric inpatients are not representative of older inpatients in China because of insufficient sample sizes or single-center study designs. The purpose of our study was to examine the prevalence of cognitive impairment and the relationship between cognitive impairment and 1-year adverse health outcomes in older inpatients. Methods This study was a large-scale multi-center cohort study conducted from October 2018 to February 2020. Six tertiary hospitals across China were selected using a two-stage cluster sampling method, and eligible older inpatients were selected for the baseline survey and follow-up. The Mini Cognitive Scale and the FRAIL scale were used to screen for cognitive impairment and frailty, respectively. The EuroQol-5 Dimension-5 Level questionnaire was used to assess health-related quality of life (HRQoL). We used a generalized estimating model to evaluate the relationship between cognitive impairment and adverse outcomes. Results The study included 5008 men (58.02%) and 3623 women (41.98%), and 70.64% were aged 65–75 years, and 26.27% were aged 75–85 years. Cognitive impairment was observed in 1756 patients (20.35%). There were significant differences between participants with cognitive impairment and those with normal cognitive function for age, gender, surgery status, frailty, depression, handgrip strength and so on. After adjusting for multiple covariates, compared with patients with normal cognitive function, the odds ratio for 1-year mortality was 1.216 (95% confidence interval [CI]: 1.076–1.375) and for 1-year incidence of frailty was 1.195 (95% CI: 1.037–1.376) in patients with cognitive impairment. Similarly, the regression coefficient of 1-year HRQoL was − 0.013 (95% CI: − 0.024−− 0.002). In the stratified analysis, risk of adverse outcome within 1 year was higher in older patients with cognitive impairment aged over 75 years than those aged 65–74 years. Conclusions We revealed that cognitive impairment was highly correlated with occurrence of 1-year adverse health outcomes (death, frailty, and decreased HRQoL) in older inpatients, which provides a basis for formulating effective intervention measures. Trial registration Chinese Clinical Trial Registry, ChiCTR1800017682 , registered 09 August 2018.